Towards a development and use of internet web and information communication technologies for veterinary medicine education in Nigeria (2006)
Various professions, such as accountancy, medicine, engineering and law, have developed and utilized the potentials and capabilities of the Internet in professional education, training, research and practice. This is by utilizing Internet Web Communication Technologies (WCT), the computers/computer networks of various Information Communication Technologies (ICT), and the development of an electronic libraries/resource base. The veterinary profession, over the past decade or so, has also utilized these facilities. However, the development and use of ICT/WCT and electronic libraries for veterinary medicine is mainly limited to the developed countries like the USA, UK and other European countries. It remains, largely an “African Dream”. This could be ascribed to the low adaptability/affordability of the Internet culture and a low level of awareness of these electronic facilities in African countries. Nigeria has five officially recognized veterinary faculties, with three others in the offing. The availability of self-owned Internet links by these universities is a recent phenomenon. However, many academics had utilized private commercial Internet facilities, a relatively expensive venture. Thus, none of the veterinary faculties in Nigeria is engaged in corporate utilization of the WCT/ICT facilities in veterinary education. Also, although the theme at the 2001 Congress of the Nigerian Veterinary Medical Association, was “Advances in Information Technology: Impact on the Veterinary Profession”, apart from an invited speaker, only one paper, presented by this author, was strictly relevant on the theme. Apart from the low adaptability/affordability and the apparent lack of awareness, there are three major limitations to the development and use of ICT/WCT/veterinary electronic libraries/ resource base in veterinary medicine in Nigeria. These are the need for training/ retraining of veterinary informatics personnel and acquisition of relevant hardware/software, poor power supply and the development of sufficient/relevant local veterinary electronic libraries. The Faculty of Veterinary Medicine, University of Ibadan, which was recently designated a Nigerian Center of Excellence in Veterinary Public Health and Preventive Medicine by the Post-Graduate College of Veterinary Surgeons Nigeria, has the human and intellectual capacity for the application of ICT and WCT to veterinary education and ongoing research in transboundary and zoonotic tropical diseases. The Faculty eagerly looks forward to such international collaborative support to overcome existing limitations, in its mission for the application of ICT and WCT to veterinary education, research and practice in Nigeria.